Influence of Acidic Substances on Compression Deformation Characteristics of Loess. (20th April 2021) - Tang, Hao; Liu, Chiyang; Wang, Nianqin; Li, Huahua; Wu, Guannan; Luo, Jinzhi; Zeng, Mengli
Abstract : Current research theories on acid-contaminated soils indicate that acids can alter the physical properties of soils, which in turn can affect their engineering mechanical properties. However, compressibility, one of the most important mechanical properties of loess, may be affected by acidic substances. To investigate the influence of acid on the compression properties of loess, this study uses a uniaxial compressor to investigate the changes of compression properties of loess under different acid concentrations and different acid immersion times and attempts to predict the causes of macroscopic compressibility changes from the microscopic pore changes of acid-etched loess. The test results show that when the soaking time is the same, the hydrochloric acid concentration increases from 0 to 3.0 mol/L, the compression coefficient C c increases by 43.20–87.5%, and the compression yield stress σ pc decreases by 51.36–60.86%; when the concentration of hydrochloric acid is the same, the soaking time increases from 1 day to 12 days, the compression coefficient C c increases by 119.05–197.46%, and compressive yield stress σ pc decreases by 10.67–22.02%. The microscopic images of loess soaked for 12 days at 3.0 mol/L hydrochloric acid concentration were compared with those of the original loess. The percentages of micropore, small pore, mesopore, and macropore areas of original loess were 20.90%, 79.10%, 0%, and 0%, respectively. The percentages of micropore, small pore, mesopore, and macropore areas of acid-etched loess were 6.24%, 37.21%, 1.14%, and 55.40%, respectively. The enhancement of the compressive properties of acid-etched loess is the result of the coupling of acid concentration and soaking time, and the change of macroscopic compressive properties may be related to the increase of microscopic macropore area after acid erosion. The results of this study can be used as a reference for the study of soil mechanical properties in acid-contaminated soils.